A Policy Strategy for Strengthening Area-Based Waste Management Institutions to Improve the Effectiveness of Waste Services in Denpasar City - Wirati, Ni Wayan (Institute for Research and Community Services Udayana University, 2026)
Waste management is a pressing issue in urban areas, including Denpasar City, which produces over 1,000 tons of waste daily. Limited infrastructure, low public participation, and weak institutional coordination have created inefficiencies in the current system. This policy paper proposes strategies to strengthen waste management institutions at the sub-district level to improve service effectiveness. Through secondary data analysis, regulatory review, and assessment of policy alternatives, the study finds that the absence of Waste Management Technical Implementation Units (UPTD) in sub-districts significantly hinders service delivery and community involvement. Of four policy options considered, establishing UPTDs simultaneously in all sub-districts is identified as the most effective and sustainable. This approach is expected to improve operational responsiveness, encourage local innovation, and support national waste management goals. Strengthening territorial-level institutions is therefore essential to developing a decentralized and sustainable waste management system in Denpasar City.